Three Essays on CEO Characteristics and Corporate Financing Decisions - Islam, Md. Ariful (Curtin University, 2020)
This thesis examines the relationship between CEO characteristics, namely CEO power, CEO outsider, with corporate financing decisions, specifically corporate cash holdings and dividend policy. The study finds that powerful CEOs prefer higher cash holdings whereas outsider CEOs are initially interested in reducing cash holdings but such CEOs revert to increasing cash holdings to tunnel cash through dividend payouts. Finally, although powerful CEOs adopt dividend payment decision, such CEOs reduce the quantum of the actual dividend.